3359 A TL1 Team Approach to Clinician Perspectives on Hoarding Disorder. (27th March 2019) - Henderson, Rebecca R; Cooke, Danielle Laine; Archer, Christian; McNamara, Joseph P.; Collings, Pete; Mathews, Carol
Abstract : OBJECTIVES/SPECIFIC AIMS: By combining clinical knowledge of hoarding disorder (HD) with qualitative methods from cultural anthropology, we hope to build a patient-centered approach that will allow us to better understand the clinician perspectives on patient motivations and explanatory models of individuals with HD, and improve treatment outcomes. We describe the ways that these methodologies are productively merged in this project as a result of TL1 collaboration, and present a preliminary picture of methodological and theoretical issues uncovered as part of this processes. We further describe the analytical methods used for this project, and explore issues raised through the combination of psychological and anthropological data and insights. METHODS/STUDY POPULATION: This study represents an attempt to combine the qualitative methodologies of cultural anthropology with the clinical knowledge of psychology and psychiatry in order to better understand gaps between provider and patient beliefs and knowledge about hoarding disorder. This study will present preliminary methodological issues arising from interviews with hoarding experts. RESULTS/ANTICIPATED RESULTS: This study will discuss preliminary issues including shared language, strengths and limitations of both disciplines, and factors for consideration when combining these disparate methodologies. It will close with recommendations for consideration when moving forward with similar collaborations. DISCUSSION/SIGNIFICANCE OF IMPACT: This project seeks to unite psychological and social factors that may contribute to the lived experience of individuals with HD in order to better understand the way that HD is manifested. It also unites disparate methodologies to provide us with a more holistic and complete picture of the experience of HD. While HD has been studied within psychiatry, it has never been assessed using the qualitative methods of anthropology. These methods provide the possibility of expanding knowledge about the ways that this disorder is experienced by individuals and their families, and potentially impacted by shared beliefs and cultures. Furthermore, qualitative data of this nature provides a patient perspective on the experience of HD as a psychiatric illness. This patient perspective can be used to better inform treatment, improve patient outcomes, and to allow providers and researchers to gain a fuller understanding of this complex population.